High-intensity focused ultrasound treatment of liver tumours: post-treatment MRI correlates well with intra-operative estimates of treatment volume. - Leslie, T; Ritchie, R; Illing, R; Ter Haar, G; Phillips, R; Middleton, M; Bch, B; Wu, F; Cranston, D (2012)
OBJECTIVES: To assess the safety and feasibility of high-intensity focused ultrasound (HIFU) ablation of liver tumours and to determine whether post-operative MRI correlates with intra-operative imaging. METHODS: 31 patients were recruited into two ethically approved clinical trials (median age 64; mean BMI 26 kg m(-2)). Patients with liver tumours (primary or metastatic) underwent a single HIFU treatment monitored using intra-operative B-mode ultrasound. Follow-up consisted of radiology and histology (surgical trial) or radiology alone (radiology trial). Radiological follow-up was digital subtraction contrast-enhanced MRI. RESULTS: Treatment according to protocol was possible in 30 of 31 patients. One treatment was abandoned because of equipment failure. Transient pain and superficial skin burns were seen in 81% (25/31) and 39% (12/31) of patients, respectively. One moderate skin burn occurred. One patient died prior to radiological follow-up. Radiological evidence of ablation was seen in 93% (27/29) of patients. Ablation accuracy was good in 89% (24/27) of patients. In three patients the zone of ablation lay ≤2 mm outside the tumour. The median cross-sectional area (CSA) of the zone of ablation was 5.0 and 5.1 cm(2) using intra-operative and post-operative imaging, respectively. The mean MRI:B-mode CSA ratio was 1.57 [95% confidence interval (CI)=0.57-2.71]. There was positive correlation between MRI and B-mode CSA (Spearman's r=0.48; 95% CI 0.11-0.73; p=0.011) and the slope of linear regression was significantly non-zero (1.23; 95% CI=0.68-1.77; p<0.0001). CONCLUSIONS: HIFU ablation of liver tumours is safe and feasible. HIFU treatment is accurate, and intra-operative assessment of treatment provides an accurate measure of the zone of ablation and correlates well with MRI follow-up.